Blasting-Induced Permeability Enhancement of Ore Deposits Associated with Low-Permeability Weakly Weathered Granites Based on the Split Hopkinson Pressure Bar. (23rd December 2018) - Yan, Lei; Yi, Wenhua; Liu, Liansheng; Liu, Jiangchao; Zhang, Shenghui
Abstract : By utilizing the improved split Hopkinson pressure bar (SHPB) test device, uniaxial, constant-speed cyclic, and variable-speed cyclic impact compression tests were conducted on weakly weathered granite samples. By combining nuclear magnetic resonance (NMR) and triaxial seepage tests, this study investigated the change laws in the mechanical properties, porosity evolution, and permeability coefficients of the samples under cyclic impacts. The results showed that in constant-speed cyclic impacts with increasing impact times, deformation modulus decreased, whilst porosity firstly decreased and then increased. Furthermore, dynamic peak strength firstly increased and then decreased whereas peak strain constantly increased before failure of the samples. In the variable-speed cyclic impacts, as impact times increased, deformation modulus firstly increased and then declined with damage occurring after four impact times. The compaction process weakened and even disappeared with increasing initial porosity. Three types of pores were found in the samples that changed in multiscale under cyclic loading. In general, small pores extended to medium- and large-sized pores. After three variable-speed cyclic impacts, the porosity of the samples was larger than the initial porosity and the permeability coefficient was greater than its initial value. The results demonstrate that the purpose of enhancing permeability and keeping the ore body stable can be achieved by conducting three variable-speed cyclic impacts on the samples.